Priority setting for small ruminant research - Reynolds, L. (International Livestock Centre for Africa, 1993)
The limited resources available to national agriculture research and extension systems in Africa will allow only top priority areas to be funded. Priority identification must take into account farmers' objectives and those of national planners. A farming systems approach is essential to determine farmers' objectives and constraints and to identify appropriate solutions. Such information is an essential prerequisite in the formulation of research programmes, which must be backed up by a thorough review of the literature. Small ruminants may or may not be a national priority.